"Taking" Informational Property Through Discovery - Gregory Gelfand (Washington University Law Quarterly, 1988)
This Article employs civil discovery under the Federal Rules of Civil Procedure" as its paradigm for testing the constitutionality of requiring the uncompensated disclosure of informational property. The section of this Article which follows defines the term "informational property" and explains the choice of that term for the purposes of the analysis of this Article. Section III sets forth the analysis employed in taking cases and the ramifications of that analysis for informational property. Section IV then considers certain counterarguments which are unique to the application of the taking analysis to informational property. Finally, Section V of this Article synthesizes the foregoing arguments, considers the appropriate remedy for bringing discovery provisions into compliance with the prohibition against uncompensated takings, and places the analysis employed in this Article in the broader context of the purpose underlying the constitutional prohibition against taking private property for public use without compensation.
Keywords: Eminent domain; Discovery (Law); Intellectual property